Analisis Penggunaan ChatGPT sebagai Sumber Informasi terhadap Literasi Kebugaran - Indah Permata Sari (Yayasan Literasi Sains Indonesia, 2026)
The rapid development of artificial intelligence, particularly ChatGPT, has created new opportunities for delivering health and fitness information. However, empirical evidence regarding its use as a fitness information source and its relationship with fitness literacy remains limited. This study aimed to analyze the associations between the frequency of ChatGPT use, information-seeking purposes, perceived usefulness of ChatGPT, and fitness literacy. The study employed a cross-sectional design with a sample of 55 respondents, consisting of members who engaged in fitness activities using a personal trainer at a location in South Tangerang. Data were collected using structured questionnaires and analyzed using descriptive and inferential statistics, including correlation tests. The results demonstrated significant positive relationships between the frequency of ChatGPT use and fitness literacy (p < 0.001), information-seeking purposes and fitness literacy (p < 0.001), and perceived usefulness of ChatGPT and fitness literacy (p < 0.001), with perceived usefulness showing the strongest association. These findings indicate that more frequent use of ChatGPT, more practical information-seeking purposes, and higher perceived usefulness are associated with higher levels of fitness literacy. In conclusion, ChatGPT has the potential to serve as an effective supportive information source for enhancing fitness literacy among physically active adults.